ANALISIS KINERJA KEUANGAN BANK DI INDONESIA SETELAH MERGER - Akbar Maulana Hadi (2022)
This research is quantitative research which aims to determine Credit Risk, Liquidity and Capital Adequacy on Financial Performance. The research population used in this study were 13 companies registered with the Financial Services Authority (OJK) for the 2016-2020 period. By using a saturated sample of 13 banking companies that merged for the 2001-2019 period with a five-year research period and obtained 65 sample units. Analysis of the data in this study using Microsoft Excel and hypothesis testing using Panel Data Analysis with E-Views 12 program and a significance level of 5%. The results of this study indicate that Credit Risk as measured by Non Performing Loans (NPL) has a negative effect on financial performance. Liquidity as measured by the Loan to Deposit Ratio (LDR) has a negative effect on financial performance. Capital Adequacy as measured by the Capital Adequacy Ratio (CAR) has no effect on financial performance.